Symmetry in Nonlinear Dynamics and Chaos II (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This compilation provides a thorough review of recent advancements in nonlinear dynamical systems and chaotic behavior. The contents of this reprint are especially pertinent for graduate students and researchers in a variety of fields, including physics, chemistry, biomedicine, social sciences, economic sciences, engineering, etc.